Towards mechanism-based interventions for auxin signaling: application of algebraic edge control to a Boolean network model - Kayoh∗†, C.O.; Ugbene†‡, I.J. (International Journal of Mathematical Analysis and Modelling, 2023)
This study developed a Boolean network model representing auxin signaling dynamics. Control techniques identified five (5) interactions that, when applied, may modulate auxin signaling dynamics. Interpreting mechanisms by which these predicted targets regulates auxin responses generated testable hypotheses regarding novel regulators. While the simplified model omits molecular details, validating predictions experimentally can inform iterative model refinements that deepen mechanistic understanding. Integrating computational modeling, control strategies and experiment-model cycles thus shows promise for developing target-based auxin interventions. This framework may inform applications beyond auxin signaling, illustrating a blueprint for progressing from abstract biological representations to meaningful mechanisms and practical tools for purposefully manipulating complex systems.